MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING KELAS XI SMA NEGERI 1 PAMEKASAN - Henny Fitriyanti (Universitas Muhammadiyah Gresik, 2020)
Basically, most students think that mathematics is an unpleasant subject, but actually it starts from suggestions received from other people. That suggestion causes students to feel tense and afraid even before receiving math lessons. The use of the lecture method used by the teacher causes students to play a less role so that they feel less excited and feel bored, their understanding is not optimal, and the scores obtained are not as expected. This study aims to improve the critical thinking of class XI students of SMAN 1 Pamekasan after participating in the discovery learning model. This classroom action research was conducted in 3 cycles, each of which consisted of one meeting. Each cycle consists of four steps, namely planning, acting, observing and reflecting. The results of this study indicate that the percentage of critical thinking scores of students in cycle I was 56% with low qualifications, increased in cycle II by 68.75% with enough qualifications, cycle III by 81,25% with high qualifications. Based on these results, it can be concluded that the indicators of success of this study are fulfilled and the application of the Discovery Learning model in online learning can improve students' critical thinking.